APPLICATION EXPERIENCE OF GOAT'S MILK BASED PRODUCTS AMONG CHILDREN, SUFFERING FROM ATOPIC DERMATITIS - T.G. Malanicheva; L.A. Khaertdinova; S.N. Denisova ("Paediatrician" Publishers LLC, 2007)
The purpose of the work is to study the efficiency of the diet therapy against atopic dermatitis by means of the goat's milk based products among children at different age. The researchers observed 188 children aged between 3 months and 18 years, suffering from atopic dermatitis aggravated by the mycotic infection. Patients of the main group (102 children under 3) received goat's milk based products within the hypo allergic diet - «Nanny» and «Nanny - Zolotaya Kozochka» adapted milk formulas, while children over 3 received «Amal Tea» instant goat's milk. The research findings have showed that the introduction of the goat's milk based products into the food ration leads not only to the positive short term results - achievement of the clinical remission on 12th-20th day from the moment the therapy starts, but also to the positive long term effect - remission extension, reduction of the disease recurrences, reduction of the general IgE level in blood serum and offending IgE allergens to the cow milk proteins and casein. Thus, the replacement of the cow milk based products within the ration of patients for «Nanny» and «Nanny - Zolotaya Kozochka» adapted milk formulas and «Amal Tea» instant goat's milk allows for optimization of the atopic dermatitis diet therapy among children at different age. Key words: atopic dermatitis, diet therapy, goat's milk.